La mossa di Pagenaud: eSports tra postumanesimo e convergenze tecnologiche, economiche, culturali - Ruffino, Paolo (Eracle. Journal of Sport and Social Sciences, 2021)
On May 2nd, 2020, the IndyCar racing competition terminates with some catastrophic car accidents. However, no driver is injured, and no car is scratched. The competition, halted by the COVID-19 pandemic, has been completed through the virtual environment of the eMotorsport simulation iRacing. This article analyses the race as a symbolic event, and as part of a historical transition where the production and consumption of sports converge with the techniques and cultures of digital gaming. In particular, we look at the emergence of digital platforms and at the assimilation of spectatorship with active participation; at the posthuman assemblages borne out of the encounter between the bodies of the e-athletes and the interfaces of the videogame; at the emergence of new forms of uncertain and quantified individualities in eSports, and at the rise of nonhuman agencies such as artificial intelligence.